Super-long-cycle energy storage semi-solid battery and preparation method thereof

By using a lithium-rich positive electrode active layer and a gel electrolyte composition in a semi-solid-state energy storage battery, the problem of poor cycle performance is solved, achieving ultra-long cycle life and efficient lithium-ion transport, making it suitable for cold regions.

CN121123360APending Publication Date: 2025-12-12SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511276566.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-08
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Existing semi-solid-state batteries for energy storage have poor cycle performance, making it difficult to meet the ultra-long cycle requirements of large cells during charge and discharge.

Method used

The battery employs a lithium-rich positive electrode active layer, coating, and gel electrolyte composition. The coating material includes lithium aluminum titanium phosphate, a first binder, and alumina. The gel electrolyte is composed of lithium salt, organic solvent, vinylene carbonate, fluoroethylene carbonate, polystyrene, and 1,3-dioxolane. A stable SEI film is formed through polymerization, which improves the lithium-ion transport rate and battery stability.

Benefits of technology

It significantly improves the battery's initial efficiency, capacity, and cycle life, extending the battery's lifespan, and it can operate normally even in cold regions, making it suitable for use in cold areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005586227390000081
    Figure BDA0005586227390000081
Patent Text Reader

Abstract

The invention provides a super-long-cycle energy storage semi-solid battery and a preparation method thereof. The energy storage semi-solid battery comprises a positive plate, a diaphragm, a gel electrolyte and a negative plate, the positive plate comprises a current collector, a lithium-rich positive active layer and a coating which are stacked in sequence, and the material of the coating comprises lithium titanium aluminum phosphate, a first binder and aluminum oxide; the gel electrolyte is obtained by polymerizing a gel electrolyte composition, and the gel electrolyte composition comprises a lithium salt, an organic solvent, vinylene carbonate, fluoroethylene carbonate, polystyrene, 1, 3-dioxolame and an initiator. The energy-storage semi-solid-state battery has excellent cycle performance, can normally operate at-20 DEG C, and is particularly suitable for being used in cold regions.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of secondary batteries, in particular to a super-long cycle energy storage semi-solid battery and a preparation method thereof. BACKGROUND

[0002] In 2024, with the rapid development of the energy storage market, the competition among lithium battery companies is becoming increasingly fierce, especially in the field of large cells, which has become the focus of many companies. Although the growth rate of the power battery market is slowing down, the energy storage market is emerging as a new growth pole for companies under the multiple driving forces of policy, economy and technology. Behind this phenomenon, not only is the pursuit of renewable energy worldwide, but also the continuous efforts of companies in technological innovation and cost control.

[0003] Under such a background, the rise of large cells has become an important trend in the industry. Such cells have higher capacity and better super-long cycle performance, which can reduce unit costs while improving the service life of the battery. In the current market, 314Ah large cells have gradually become mainstream, and their use in energy storage systems is increasing, showing broad application prospects.

[0004] Of course, while technology brings opportunities, it also brings challenges. The super-long cycle of large cells during charging and discharging puts higher requirements on the research and production processes of companies. How to ensure the consistency and super-long cycle life of the cells has become a key to further promoting large cells. At the same time, as the market matures, the total life cycle cost of products will become an important indicator that companies must pay attention to, and the sustainability of relying solely on price reduction strategies is also questioned. SUMMARY

[0005] The main purpose of the present application is to provide a super-long cycle energy storage semi-solid battery and a preparation method thereof, to solve the problem of poor cycle performance of the existing energy storage semi-solid battery.

[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present application, a super-long cycle energy storage semi-solid battery is provided, comprising a positive electrode sheet, a separator, a gel electrolyte and a negative electrode sheet, the positive electrode sheet comprising a current collector, a lithium-rich positive electrode active layer and a coating layer stacked in turn, wherein the material of the coating layer comprises lithium aluminum titanium phosphate, a first binder and aluminum oxide; the gel electrolyte is obtained by polymerization of a gel electrolyte composition, and the gel electrolyte composition comprises a lithium salt, an organic solvent, a vinylene carbonate, a fluoroethylene carbonate, a polystyrene, a 1,3-dioxolane and an initiator.

[0007] Further, the material of the above-mentioned lithium-rich positive electrode active layer comprises a positive electrode active material, a second binder, a conductive agent, a carbon nanotube and a lithium supplementing agent.

[0008] Furthermore, the mass ratio of the above-mentioned positive electrode active material, the second binder, the conductive agent, the carbon nanotube and the lithium supplement is (94.16~95.26):(1.44~1.5):(0.28~0.3):(0.02~0.04):(3~4).

[0009] Further, the above-mentioned positive electrode active material is selected from lithium iron phosphate and / or lithium manganese iron phosphate; and / or, the lithium replenishing agent is selected from any one or more of Li2NiO2, Li5FeO4, Li5NiO4 and Li6CoO4; preferably, the lithium replenishing agent is a combination of Li2NiO2 and Li5FeO4, and the mass ratio of Li2NiO2 to Li5FeO4 is (2~2.5):(1~1.5); and / or, the second binder is selected from any one or more of polyvinylidene fluoride, polyacrylic acid and polyaniline; and / or, the conductive agent is selected from any one or more of super conductive carbon black, Ketjen black, acetylene black and carbon nanotubes.

[0010] Further, the mass ratio of the above-mentioned lithium aluminum titanium phosphate, the first binder and alumina is (85-87):(8-10):(3-5); preferably, the first binder is selected from any one or more of polyvinylidene fluoride, polyacrylic acid and polyaniline.

[0011] Furthermore, the thickness of the above coating is 2 to 4 μm; and / or, the thickness of the lithium-rich positive electrode active layer is 204 to 208 μm.

[0012] Furthermore, the mass ratio of the lithium salt, organic solvent, vinylene carbonate, fluorovinyl carbonate, polystyrene, 1,3-dioxolane and initiator is (14-14.5):63:(2.5-3):(4-5):(1-3):(12-14):(1-3).

[0013] Further, the lithium salt is selected from any one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium difluorooxalate borate; and / or, the organic solvent is selected from any one or more of dimethyl carbonate, ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate; preferably, the organic solvent is a combination of dimethyl carbonate, ethylene carbonate, and methyl ethyl carbonate, and the mass ratio of dimethyl carbonate, ethylene carbonate, and methyl ethyl carbonate is (32-34):(16-18):(11-15); and / or, the initiator is selected from azobisisobutyronitrile and / or azobisisoheptanenitrile.

[0014] According to another aspect of the present invention, a method for preparing the aforementioned energy storage semi-solid-state battery is provided, the method comprising: step S1, coating a lithium-rich positive electrode slurry onto the surface of a current collector and drying it to form a lithium-rich positive electrode active layer; step S2, mixing lithium aluminum titanium phosphate, a first binder, alumina, and a solvent to obtain a coating slurry; spraying the coating slurry onto the side of the lithium-rich positive electrode active layer away from the current collector and drying it to form a coating to obtain a positive electrode sheet; step S3, preparing a dry cell from the positive electrode sheet, a negative electrode sheet, and a separator; step S4, mixing a lithium salt, an organic solvent, vinylene carbonate, fluoroethylene carbonate, polystyrene, 1,3-dioxolane, and an initiator to obtain a gel electrolyte composition; and step S5, injecting the gel electrolyte composition into the dry cell for polymerization to obtain an energy storage semi-solid-state battery.

[0015] Further, the solvent is N-methylpyrrolidone; and / or, the solid content of the coating slurry is 30-32%; and / or, the polymerization temperature is 60-85°C; and / or, the polymerization time is 6-24 h.

[0016] The presence of a lithium-rich positive electrode active layer in this application helps increase the reversible active lithium content, thereby improving the battery's initial efficiency, capacity, and cycle life. The coating helps accelerate lithium-ion transport rates and improve battery reaction kinetics; simultaneously, it helps reduce the probability of electrolyte corrosion of the positive electrode active material, thus reducing internal side reactions. The presence of vinylene carbonate in the gel electrolyte composition helps form a stable SEI film, and the presence of fluoroethylene carbonate helps further optimize the SEI film. The synergistic effect of vinylene carbonate and fluoroethylene carbonate helps further improve the cycle stability of the energy storage semi-solid-state battery. The main purpose of adding polystyrene is as a thickener and viscosity modifier to improve the physical stability of the gel electrolyte. The presence of 1,3-dioxolane helps improve the conductivity and low-temperature performance of the gel electrolyte, and it forms the gel electrolyte matrix through ring-opening polymerization. The chemical stability and mechanical strength of the semi-solid-state battery help reduce battery degradation during charge and discharge processes, thereby extending battery life. The gel electrolyte material used in this application is non-toxic, harmless, easy to recycle and reuse, and can operate normally in energy storage semi-solid batteries at -20℃, making it particularly suitable for use in cold regions. Detailed Implementation

[0017] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the embodiments.

[0018] As analyzed in the background section of this application, the existing semi-solid-state energy storage batteries have poor cycle performance. To solve this problem, this application provides an ultra-long cycle semi-solid-state energy storage battery and its preparation method.

[0019] In a typical embodiment of this application, an ultra-long cycle energy storage semi-solid battery is provided, comprising a positive electrode, a separator, a gel electrolyte, and a negative electrode. The positive electrode comprises a current collector, a lithium-rich positive electrode active layer, and a coating stacked sequentially. The coating material includes lithium aluminum titanium phosphate, a first binder, and alumina. The gel electrolyte is obtained by polymerizing a gel electrolyte composition, which includes a lithium salt, an organic solvent, vinylene carbonate, fluoroethylene carbonate, polystyrene, 1,3-dioxolane, and an initiator.

[0020] The presence of a lithium-rich positive electrode active layer in this application helps increase the reversible active lithium content, thereby improving the battery's initial efficiency, capacity, and cycle life. The coating helps accelerate lithium-ion transport rates and improve battery reaction kinetics; simultaneously, it helps reduce the probability of electrolyte corrosion of the positive electrode active material, thus reducing internal side reactions. The presence of vinylene carbonate in the gel electrolyte composition helps form a stable SEI film, and the presence of fluoroethylene carbonate helps further optimize the SEI film. The synergistic effect of vinylene carbonate and fluoroethylene carbonate helps further improve the cycle stability of the energy storage semi-solid-state battery. The main purpose of adding polystyrene is as a thickener and viscosity modifier to improve the physical stability of the gel electrolyte. The presence of 1,3-dioxolane helps improve the conductivity and low-temperature performance of the gel electrolyte, and it forms the gel electrolyte matrix through ring-opening polymerization. The chemical stability and mechanical strength of the semi-solid-state battery help reduce battery degradation during charge and discharge processes, thereby extending battery life. The gel electrolyte material used in this application is non-toxic, harmless, easy to recycle and reuse, and can operate normally in energy storage semi-solid batteries at -20℃, making it particularly suitable for use in cold regions.

[0021] In this application, the coating on the positive electrode sheet is in direct contact with the gel electrolyte on the side away from the lithium-rich positive electrode active layer.

[0022] In order to further improve the stability of the gel electrolyte and thus further improve the cycle stability of the energy storage semi-solid battery, in one embodiment of this application, the number average molecular weight of the polystyrene is 200,000 to 300,000 g / mol.

[0023] In one embodiment of this application, the materials of the lithium-rich positive electrode active layer include a positive electrode active material, a second binder, a conductive agent, carbon nanotubes, and a lithium replenishing agent.

[0024] The presence of lithium supplements helps improve the cycle stability of semi-solid-state energy storage batteries.

[0025] In one embodiment of this application, the mass ratio of the above-mentioned positive electrode active material, second binder, conductive agent, carbon nanotube and lithium supplementer is (94.16~95.26):(1.44~1.5):(0.28~0.3):(0.02~0.04):(3~4).

[0026] Controlling the mass ratio of the positive electrode active material, the second binder, the conductive agent, the carbon nanotubes, and the lithium replenishing agent within the above range helps to improve the synergistic effect between the components, thereby helping to further improve the cycle performance of the energy storage semi-solid-state battery.

[0027] To further improve the cycle stability of the energy storage semi-solid-state battery, in one embodiment of this application, the above-mentioned positive electrode active material is selected from lithium iron phosphate and / or lithium manganese iron phosphate; and / or, the lithium replenishing agent is selected from any one or more of Li2NiO2, Li5FeO4, Li5NiO4 and Li6CoO4; preferably, the lithium replenishing agent is a combination of Li2NiO2 and Li5FeO4, and the mass ratio of Li2NiO2 to Li5FeO4 is (2~2.5):(1~1.5); and / or, the second binder is selected from any one or more of polyvinylidene fluoride polyacrylic acid and polyaniline; and / or, the conductive agent is selected from any one or more of super conductive carbon black, Ketjen black, acetylene black and carbon nanotubes.

[0028] In one embodiment of this application, the mass ratio of the above-mentioned lithium aluminum titanium phosphate, the first binder and alumina is (85-87):(8-10):(3-5); preferably, the first binder is selected from any one or more of polyvinylidene fluoride, polyacrylic acid and polyaniline.

[0029] The presence of lithium aluminum titanium phosphate helps accelerate the transport rate of lithium ions between the positive and negative electrodes, thereby optimizing the battery's reaction kinetics and improving its charge-discharge efficiency and power response speed. The presence of alumina helps isolate the positive electrode material from the electrolyte, especially suppressing side reactions between deposited lithium and the electrolyte. It also helps improve the coating's heat resistance and chemical stability. Controlling the mass ratio of lithium aluminum titanium phosphate, the first binder, and alumina within the aforementioned range helps enhance the interaction between the components, thus further improving the cycle stability of the semi-solid-state energy storage battery.

[0030] In one embodiment of this application, the thickness of the coating is 2 to 4 μm; and / or, the thickness of the lithium-rich positive electrode active layer is 204 to 208 μm.

[0031] Controlling the coating thickness within the aforementioned range helps to provide effective mechanical and chemical barriers while reducing resistance to lithium-ion transport, thus optimizing the migration efficiency of lithium-ions between the positive and negative electrodes. Controlling the thickness of the lithium-rich positive electrode active layer within the aforementioned range also helps to improve the utilization rate of the lithium-rich positive electrode active layer, thereby contributing to increased energy density and storage capacity of semi-solid-state batteries.

[0032] In one embodiment of this application, the mass ratio of the lithium salt, organic solvent, vinylene carbonate, fluorovinyl carbonate, polystyrene, 1,3-dioxolane and initiator is (14-14.5):63:(2.5-3):(4-5):(1-3):(12-14):(1-3).

[0033] Controlling the mass ratio of lithium salt, organic solvent, vinylene carbonate, fluoroethylene carbonate, polystyrene, 1,3-dioxolane, and initiator within the above range helps to improve the synergistic effect between the components, thereby helping to form a stable SEI film on the electrode surface while improving the stability of the gel electrolyte, and further helping to improve the cycle stability of the energy storage semi-solid-state battery.

[0034] To further improve the stability of the gel electrolyte, in one embodiment of this application, the lithium salt is selected from any one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, and lithium difluorooxalate borate; and / or, the organic solvent is selected from any one or more of dimethyl carbonate, ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate; preferably, the organic solvent is a combination of dimethyl carbonate, ethylene carbonate, and ethyl methyl carbonate, and the mass ratio of dimethyl carbonate, ethylene carbonate, and ethyl methyl carbonate is (32-34):(16-18):(11-15); and / or, the initiator is selected from azobisisobutyronitrile and / or azobisisoheptanenitrile.

[0035] Including but not limited to, the above-mentioned negative electrode sheet is a graphite negative electrode sheet, and the separator is a polyethylene separator. It should be noted that all the raw materials used in this application can be obtained by purchasing or by using existing technology.

[0036] In another typical embodiment of this application, a method for preparing the aforementioned energy storage semi-solid-state battery is provided. The method includes: step S1, coating a lithium-rich positive electrode slurry onto the surface of a current collector and drying it to form a lithium-rich positive electrode active layer; step S2, mixing lithium aluminum titanium phosphate, a first binder, alumina, and a solvent to obtain a coating slurry; spraying the coating slurry onto the side of the lithium-rich positive electrode active layer away from the current collector and drying it to form a coating to obtain a positive electrode sheet; step S3, preparing a dry cell from the positive electrode sheet, a negative electrode sheet, and a separator; step S4, mixing a lithium salt, an organic solvent, vinylene carbonate, fluoroethylene carbonate, polystyrene, 1,3-dioxolane, and an initiator to obtain a gel electrolyte composition; and step S5, injecting the gel electrolyte composition into the dry cell for polymerization to obtain an energy storage semi-solid-state battery.

[0037] The method for preparing the energy storage semi-solid battery of this application is simple and low in cost. Furthermore, by spraying the coating slurry onto the side of the lithium-rich positive electrode active layer away from the current collector, this application helps to improve the uniformity of the coating thickness, thereby further improving the stability and consistency of the energy storage semi-solid battery.

[0038] In one embodiment of this application, the solvent is N-methylpyrrolidone; and / or, the solid content of the coating slurry is 30-32%; and / or, the polymerization temperature is 60-85°C; and / or, the polymerization time is 6-24 hours.

[0039] Controlling the type of solvent within the above-mentioned range helps to improve the uniformity of dispersion of lithium aluminum titanium phosphate, the first binder, and alumina; controlling the solid content of the coating slurry within the above-mentioned range helps to improve spraying efficiency. Controlling the polymerization temperature and time within the above-mentioned range helps to improve the stability of the gel electrolyte.

[0040] The beneficial effects of this application will be further illustrated below with reference to the embodiments.

[0041] Example 1

[0042] Lithium iron phosphate, polyvinylidene fluoride, super conductive carbon black, carbon nanotubes, and lithium supplementer were mixed in N-methylpyrrolidone at a mass ratio of 95.26:1.44:0.28:0.02:3. The lithium supplementer was a combination of Li2NiO2 and Li5FeO4 at a mass ratio of 2:1, resulting in a lithium-rich cathode slurry. The lithium-rich cathode slurry was coated onto the surface of a copper foil and dried to form a lithium-rich cathode active layer with a thickness of 206 μm. Lithium aluminum titanium phosphate, polyvinylidene fluoride, and alumina were mixed in N-methylpyrrolidone at a mass ratio of 85:10:5 to obtain a coating slurry with a solid content of 32%. The coating slurry was sprayed onto the side of the lithium-rich cathode active layer away from the copper foil and dried to form a coating with a thickness of 2 μm, resulting in the cathode sheet. A dry cell was prepared by using a positive electrode, a graphite negative electrode, and a polyethylene separator. Lithium hexafluorophosphate, an organic solvent, vinylene carbonate, fluoroethylene carbonate, polystyrene (number average molecular weight of 200,000 g / mol), 1,3-dioxolane, and azobisisobutyronitrile were mixed in a mass ratio of 14:63:3:4:3:12:1. The organic solvent was a combination of dimethyl carbonate, ethylene carbonate, and methyl ethyl carbonate, with a mass ratio of 32:16:15. This yielded a gel electrolyte composition, which was then injected into the dry cell for polymerization at 85°C for 16 hours, resulting in a semi-solid-state energy storage battery.

[0043] Example 2

[0044] The difference from Example 1 is that the mass ratio of lithium iron phosphate, polyvinylidene fluoride, super conductive carbon black, carbon nanotubes and lithium supplement is 94.16:1.5:0.3:0.04:4, resulting in a semi-solid-state energy storage battery.

[0045] Example 3

[0046] The difference from Example 1 is that the mass ratio of lithium iron phosphate, polyvinylidene fluoride, super conductive carbon black, carbon nanotubes and lithium replenishing agent is 93.16:1.5:0.3:0.04:5, and a semi-solid-state energy storage battery is finally obtained.

[0047] Example 4

[0048] The difference from Example 1 is that the mass ratio of Li2NiO2 to Li5FeO4 is 2.5:1, resulting in a semi-solid-state energy storage battery.

[0049] Example 5

[0050] The difference from Example 1 is that the mass ratio of Li2NiO2 to Li5FeO4 is 3:1, resulting in a semi-solid-state energy storage battery.

[0051] Example 6

[0052] The difference from Example 1 is that the mass ratio of lithium aluminum titanium phosphate, polyvinylidene fluoride and alumina is 87:10:3, resulting in a semi-solid-state energy storage battery.

[0053] Example 7

[0054] The difference from Example 1 is that the mass ratio of lithium aluminum titanium phosphate, polyvinylidene fluoride and alumina is 87:11:2, resulting in a semi-solid-state energy storage battery.

[0055] Example 8

[0056] The difference from Example 1 is that the coating thickness is 4μm, resulting in a semi-solid-state energy storage battery.

[0057] Example 9

[0058] The difference from Example 1 is that the coating thickness is 1 μm, resulting in a semi-solid-state energy storage battery.

[0059] Example 10

[0060] The difference from Example 1 is that lithium hexafluorophosphate, organic solvent, vinylene carbonate, fluoroethylene carbonate, polystyrene, 1,3-dioxolane and azobisisobutyronitrile are in a mass ratio of 14.5:63:2.5:4:3:12:1, resulting in a semi-solid-state energy storage battery.

[0061] Example 11

[0062] The difference from Example 1 is that lithium hexafluorophosphate, organic solvent, vinylene carbonate, fluoroethylene carbonate, polystyrene, 1,3-dioxolane and azobisisobutyronitrile are in a mass ratio of 15:63:2:4:3:12:1 to finally obtain a semi-solid-state energy storage battery.

[0063] Example 12

[0064] The difference from Example 1 is that the number average molecular weight of polystyrene is 300,000 g / mol, and a semi-solid-state energy storage battery is finally obtained.

[0065] Example 13

[0066] The difference from Example 1 is that the number average molecular weight of polystyrene is 301000 g / mol, and a semi-solid-state energy storage battery is finally obtained.

[0067] Comparative Example 1

[0068] The difference from Example 1 is that the addition of lithium replenishing agent is cancelled, and the missing mass of lithium replenishing agent is replaced by lithium iron phosphate, and finally a semi-solid-state energy storage battery is obtained.

[0069] Comparative Example 2

[0070] The difference from Example 1 is that the addition of fluoroethylene carbonate is omitted, and the missing mass of fluoroethylene carbonate is replaced by vinylene carbonate, ultimately resulting in a semi-solid-state energy storage battery.

[0071] Comparative Example 3

[0072] The difference from Example 1 is that the coating slurry is not sprayed on the side of the lithium-rich positive electrode active layer away from the copper foil. Instead, the copper foil coated with the lithium-rich positive electrode active layer is used directly as the positive electrode sheet, and a semi-solid-state energy storage battery is finally obtained.

[0073] Performance testing

[0074] The specific capacity of the first discharge at 25℃, the capacity retention rate after 6000 cycles at 25℃, the specific capacity of the first discharge at -20℃, and the capacity retention rate after 6000 cycles at -20℃ were tested according to GB 44240-2024 standard. The test conditions for the specific capacity of the first discharge at 25℃ were (1) resting for 10 min, (2) charging at 0.5P constant power to the upper limit voltage (3.65V), (3) resting for 60 min, and (4) discharging at 0.5P constant power to the lower limit voltage (2.5V). The test conditions for the specific capacity of the first discharge at -20℃ were (1) resting for 10 min, (2) charging at 0.5P constant power to the lower limit voltage (2.5V). (2) Charge the battery with 0.5P constant power to the upper limit voltage (3.65V), (3) let it stand for 60 minutes, (4) discharge the battery with 0.5P constant power to the lower limit voltage (2.0V); The test conditions for the capacity retention rate of 6000 cycles at 25℃ and the capacity retention rate of 6000 cycles at -20℃ are (1) let it stand for 10 minutes, (2) charge the battery with 0.5P constant power to the upper limit voltage (3.65V), (3) let it stand for 60 minutes, (4) discharge the battery with 0.5P constant power to the lower limit voltage (2.5V), (5) let it stand for 60 minutes as one cycle, and then charge it. The test results are shown in Table 1.

[0075] Table 1

[0076]

[0077] The energy storage semi-solid-state battery of this application retains more than 90% of its capacity after 6,000 cycles at 25°C and more than 80% of its capacity after 6,000 cycles at -20°C, which is considered an ultra-long cycle life semi-solid-state battery in the industry.

[0078] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects:

[0079] The presence of a lithium-rich positive electrode active layer in this application helps increase the reversible active lithium content, thereby improving the battery's initial efficiency, capacity, and cycle life. The coating helps accelerate lithium-ion transport rates and improve battery reaction kinetics; simultaneously, it helps reduce the probability of electrolyte corrosion of the positive electrode active material, thus reducing internal side reactions. The presence of vinylene carbonate in the gel electrolyte composition helps form a stable SEI film, and the presence of fluoroethylene carbonate helps further optimize the SEI film. The synergistic effect of vinylene carbonate and fluoroethylene carbonate helps further improve the cycle stability of the energy storage semi-solid-state battery. The main purpose of adding polystyrene is as a thickener and viscosity modifier to improve the physical stability of the gel electrolyte. The presence of 1,3-dioxolane helps improve the conductivity and low-temperature performance of the gel electrolyte, and it forms the gel electrolyte matrix through ring-opening polymerization. The chemical stability and mechanical strength of the semi-solid-state battery help reduce battery degradation during charge and discharge processes, thereby extending battery life. The gel electrolyte material used in this application is non-toxic, harmless, easy to recycle and reuse, and can operate normally in energy storage semi-solid batteries at -20℃, making it particularly suitable for use in cold regions.

[0080] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A semi-solid-state energy storage battery with ultra-long cycle life, comprising a positive electrode, a separator, a gel electrolyte, and a negative electrode, characterized in that, The positive electrode sheet includes a current collector, a lithium-rich positive electrode active layer and a coating layer stacked sequentially, wherein the coating material includes lithium aluminum titanium phosphate, a first binder and aluminum oxide; The gel electrolyte is obtained by polymerizing a gel electrolyte composition, which includes a lithium salt, an organic solvent, vinylene carbonate, fluorovinyl carbonate, polystyrene, 1,3-dioxolane, and an initiator.

2. The energy storage semi-solid-state battery according to claim 1, characterized in that, The materials of the lithium-rich positive electrode active layer include positive electrode active material, second binder, conductive agent, carbon nanotubes and lithium supplementation agent.

3. The energy storage semi-solid-state battery according to claim 2, characterized in that, The mass ratio of the positive electrode active material, the second binder, the conductive agent, the carbon nanotubes, and the lithium supplement is (94.16–95.26):(1.44–1.5): (0.28~0.3):(0.02~0.04):(3~4)。 4. The energy storage semi-solid-state battery according to claim 2 or 3, characterized in that, The positive electrode active material is selected from lithium iron phosphate and / or lithium manganese iron phosphate; And / or, the lithium replenishing agent is selected from any one or more of Li2NiO2, Li5FeO4, Li5NiO4 and Li6CoO4; preferably, the lithium replenishing agent is a combination of Li2NiO2 and Li5FeO4, and the mass ratio of Li2NiO2 to Li5FeO4 is (2~2.5):(1~1.5); And / or, the second adhesive is selected from any one or more of polyvinylidene fluoride, polyacrylic acid, and polyaniline; And / or, the conductive agent is selected from any one or more of superconducting carbon black, Ketjen black, acetylene black and carbon nanotubes.

5. The energy storage semi-solid-state battery according to any one of claims 1 to 4, characterized in that, The mass ratio of the lithium aluminum titanium phosphate, the first binder, and the alumina is (85-87):(8-10):(3-5); Preferably, the first adhesive is selected from any one or more of polyvinylidene fluoride, polyacrylic acid, and polyaniline.

6. The energy storage semi-solid-state battery according to any one of claims 1 to 5, characterized in that, The coating has a thickness of 2–4 μm; and / or the lithium-rich positive electrode active layer has a thickness of 204–208 μm.

7. The energy storage semi-solid-state battery according to any one of claims 1 to 6, characterized in that, The mass ratio of the lithium salt, the organic solvent, the vinylene carbonate, the fluorovinyl carbonate, the polystyrene, the 1,3-dioxolane, and the initiator is (14-14.5):63:(2.5-3):(4-5):(1-3):(12-14):(1-3).

8. The energy storage semi-solid-state battery according to any one of claims 1 to 7, characterized in that, The lithium salt is selected from any one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide and lithium difluorooxalateborate. And / or, the organic solvent is selected from any one or more of dimethyl carbonate, ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate; preferably, the organic solvent is a combination of dimethyl carbonate, ethylene carbonate, and methyl ethyl carbonate, and the mass ratio of dimethyl carbonate, ethylene carbonate, and methyl ethyl carbonate is (32-34):(16-18). (11~15); And / or, the initiator is selected from azobisisobutyronitrile and / or azobisisoheptanenitrile.

9. A method for preparing a semi-solid-state energy storage battery according to any one of claims 1 to 8, characterized in that, The preparation method includes: Step S1: Coat the surface of the current collector with lithium-rich cathode slurry and dry it to form a lithium-rich cathode active layer. Step S2: Mix lithium aluminum titanium phosphate, first binder, alumina and solvent to obtain coating slurry; spray the coating slurry onto the side of the lithium-rich positive electrode active layer away from the current collector, dry it to form a coating, and obtain a positive electrode sheet; Step S3: The positive electrode, negative electrode, and separator are prepared into a dry battery cell; Step S4: Lithium salt, organic solvent, vinylene carbonate, fluorovinyl carbonate, polystyrene, 1,3-dioxolane and initiator are mixed to obtain a gel electrolyte composition. Step S5: Inject the gel electrolyte composition into the dry cell for polymerization to obtain the energy storage semi-solid battery.

10. The preparation method according to claim 9, characterized in that, The solvent is N-methylpyrrolidone; And / or, the solid content of the coating slurry is 30-32%; And / or, the polymerization temperature is 60–85°C; and / or, the polymerization time is 6–24 h.